2012
DOI: 10.1089/dna.2011.1246
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Arg399Gln Gene Polymorphism and the Risk of Systemic Lupus Erythematosus in the Polish Population

Abstract: It has been shown that DNA repair is reduced in patients with systemic lupus erythematosus (SLE) and that the X-ray repair cross-complementing (XRCC1) Arg399Gln (rs25487) polymorphism may contribute to DNA repair. We evaluated the frequency of the XRCC1 Arg399Gln substitution in patients with SLE (n = 265) and controls (n = 360) in a sample of the Polish population. The odds ratio (OR) for SLE patients with the Gln/Gln versus Gln/Arg or Arg/Arg genotypes was 1.553 (95% confidence interval [CI] = 0.9573-2.520;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…Moreover, there is no correlation between XRCC1 Arg399Gln, XRCC3 Thr241Met, and XRCC4 Ile401Thr polymorphisms and SLE, although they found that the XRCC1Gln/Gln and Arg/Gln genotypes are associated with the presence of anti-double-strand DNA antibody in the Brazilian population . Furthermore, the Gln allele of XRCC1 Arg399Gln polymorphism is associated with SLE and Malar rash/photosensitivity manifestations in the Polish population Warchol et al, 2012). A meta-analysis about the effect of XRCC1 Arg399Gln polymorphism in SLE susceptibility in the Brazilian, Taiwanese, Han Chinese, and Polish populations shows that the Gln/Gln or Gln/Arg genotypes and Gln allele are associated with SLE susceptibility.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, there is no correlation between XRCC1 Arg399Gln, XRCC3 Thr241Met, and XRCC4 Ile401Thr polymorphisms and SLE, although they found that the XRCC1Gln/Gln and Arg/Gln genotypes are associated with the presence of anti-double-strand DNA antibody in the Brazilian population . Furthermore, the Gln allele of XRCC1 Arg399Gln polymorphism is associated with SLE and Malar rash/photosensitivity manifestations in the Polish population Warchol et al, 2012). A meta-analysis about the effect of XRCC1 Arg399Gln polymorphism in SLE susceptibility in the Brazilian, Taiwanese, Han Chinese, and Polish populations shows that the Gln/Gln or Gln/Arg genotypes and Gln allele are associated with SLE susceptibility.…”
Section: Discussionmentioning
confidence: 95%
“…DNA repair genes can contribute to SLE predisposition (Herrick et al, 1995), and polymorphisms of XRCC1, XRCC3, and XRCC4 genes are associated with manifestation of SLE Lin et al, 2009;Warchol et al, 2012;Salimi et al, 2014). Moreover, there are numerous variants in XRCC5, XRCC6, and XRCC7 genes, which have been associated with different diseases, such as gastric cancer (Lim et al, 2002), head and neck cancer (Chang et al, 2006), breast cancer (Fu et al, 2003), glioma (Wang et al, 2004), and AML (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with ESRD, DNA damage has been shown by numerous biomarkers, such as the analysis of sister chromatid exchange and chromosomal aberrations, 37 comet assay (single-cell gel electrophoresis) in peripheral lymphocytes, 21 8-hydroxy 2-deoxyguanosine content in leukocytes 38 and mitochondrial DNA deletions in skeletal muscle. Moreover, the XRCC1 399Gln gene variant has been associated with arthrosclerotic coronary artery disease, schizophrenia, pterygium, cataracts and systemic lupus erythematosus 3,[39][40][41] as well as various cancer types such as breast, lung, prostate, renal, carcinomas of head and neck, stomach, colon and acute lymphoblastic leukemia. [42][43][44][45][46][47][48][49] Combinations of common genetic polymorphisms may increase or decrease the susceptibility to certain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair enzymes monitor the DNA structure to correct damaged nucleotide produced by methylation, oxidation or oxidative damage; therefore, DNA repair mechanisms have an essential role in genome stability (7). X-ray crosscomplementing 1 (XRCC1) is one of the DNA repair genes that may play a critical role in SLE (8). The main goal of this letter was to review the possible impacts of XRCC1 polymorphisms on SLE.…”
mentioning
confidence: 99%
“…In the first investigation, Bassi et al could not show the association of XRCC1 polymorphism (rs25487) between SLE and healthy Brazilian individuals (10). Other investigations by Lin et al and Warchol et al showed that Arg/Arg genotype of rs25487 had a protective role against SLE in Chinese and Polish populations (8,11). In the Iranian population, only one investigation was done, in which Salimi et al showed that Arg/Gln had a protective role against SLE (6).…”
mentioning
confidence: 99%